Self-Organisation Initiatives In Community-Based Conservation: A Case Study Of Bung Jagoi Hertiage Bau, Sarawak Malaysia - Ahi, Sarok; Fredicia Beatrice, Britin (Institute of Borneo Studies, UNIMAS, 2016)
This article examines the small-scaled, village-based, self-organised initiatives community-based conservation (CBC) of Bung Jagoi Heritage, Bau, Sarawak. The community self-organisation criteria are adopted in this study. The initiatives are developed through the CBC Projects under the Equator Initiative (EI) of the United Nation Development Programme (UNDP) which are considered successful by the EI. This article also investigates the impact of Bidayuh customary law or adat on the access and forest resources management in the communal forest of Bung Jagoi Heritage which utilised the Adat Bidayuh Order, 1994 and native customs as their guidelines for managing the access and forest resources. The level of participation among the villagers and the committee members is also assessed in this study based on the widely used participation typology developed by Jules N. Pretty. The data for this study is gathered through semi-structured interviews (SSIs) and observation. The findings of this study shows that the self-organisation in CBC of Bung Jagoi Heritage is initiated by a small number of Jagoi-Duyoh villagers due to some outsiders’ mysterious visits and concerns to conserve the forested land that also situate an ancestral village and its biodiversity as well as to develop the Bung Jagoi Heritage through the conservation activities. The success of this CBC self-organisation relies heavily on the involvement and commitment of the committee members, funding from the local and international donors, and leadership of the committee’s advisor in order for it to sustain and develop. The local community practices collectively known as the adat gives some impact on the access and forest resources through its communal tenure and traditional beliefs. The level of participation among the villagers can be categorised as ‘participation for material incentive’ while the level of participation among the committee member can be categorised as ‘self-mobilisation’.